Ciclos escolares, Escola Cabana e temas geradores - CARMO, Luiz Felipe do (2006)
This academic work of end of the master's degree course tried to capture how it comes if processing the reorganization of the Brazilian fundamental school with the perspective of the implantation of the regime of cycles, in peculiar of the regime of formation cycles. He tried to detach the relationships between education and politics with the intention of revealing the difficulties that intervened in the transition of the serial regime to the regime of cycles. He marked the experiences that more they stood out in the implementation of the cycles, especially those that more radicalized this change possibility in the school structure. This road was adopted in the understanding that the space of the representations and of the culture, as well as of the theoretical foundations and of the political intentions that composed the list of the configurations in that they were based the different ones proposed of cycles, they advanced, in some measured, the possibilities and the limitations of those proposals. Some experiences of the second half of the century XX, and, especially, of the decade of 1990, they are recovered. Pioneering initiatives in the adoption of school cycles, in different times and spaces, they are revisited, making possible a panoramic vision of the same ones, their multiple determinations and the contradictory scenery in that the same ones got entangled. Tends as methodology the semi-structured interview, the observation and the documental and bibliographical analysis, it accomplished a historical recovery of the political-pedagogic foundations of the implantation of the cycles in the city Belém of the Pará, with prominence for Escola Cabana's proposal (1997-2004), ending with a case study in an outlying school of the Municipal Net of Belém, where it investigated on the pertinence of the Project Interdisciplinary with Temas Geradores as center of the construction of the school curriculum. This work also reveals that the distance between the official proposal and the school practice, between the plan of the orientations and the school daily practice in itself, needs of more attention of those than they have responsibility with the education public politics, under penalty of they just capture the phenomenon and the superficiality, leaving the concrete-real in the twilight.